Vaccinations and inflammatory bowel disease – a systematic review. Issue 9 (September 2021) - Chan, Webber; Salazar, Ennaliza; Lim, Teong Guan; Ong, Wan Chee; Shim, Hang Hock
Abstract: Introduction: Patients with inflammatory bowel disease(IBD) are at risk of infections, many of which are preventable with vaccinations. We performed a systematic review on various aspects of vaccination in IBD. Methods: We searched PubMed, and EMBASE databases, through 31 January 2021. Primary outcomes included vaccination rates, predictors of vaccination, reasons of vaccination hesitancy and acceptance, and outcomes of intervention. Findings were presented with medians, ranges, and narrative synthesis. Results: We included 33 observational studies comprising 146, 918 patients and 681 physicians. The median vaccination rates of influenza, pneumococcal pneumonia, and hepatitis B vaccines were 42%(IQR, 28%–61.5%), 20%(IQR, 9%–38.5%), and 48%(IQR, 29%–53%), respectively. Uses of immunosuppressant, older age and physician recommendations have positive influence on vaccination rate. Lack of vaccine-related knowledge and awareness of need for vaccination are main reasons of vaccine hesitancy among patients and physicians. There was disagreement between gastroenterologists and primary-care physicians on whose responsibility to offer vaccination. Education was the sole intervention identified, with variable success. Conclusion: This systematic review demonstrates that the vaccination rates of IBD patients, similar to other chronic diseases, are suboptimal. Lack of vaccine-related knowledge and awareness of the need for vaccination are main reasons of vaccine hesitancy amongst patients and physicians. Education, though effective, was the only available intervention identified. Gastroenterologist could take the lead in educating, and initiating vaccination among IBD patients.